An ounce of prevention for a pound of cure: Basic health care and efficiency in health systems - Antonella Bancalari; Pedro Bernal; Pablo A. Celhay; Sebastian Martinez; Maria Deni Sánchez (Inter-American Development Bank (IDB), 2024)
We examine the efficiency gains in health systems generated after the national roll out of basic healthcare in El Salvador between 2010 and 2013. Using data from over 120 million consultations and five million hospitalizations, we demonstrate that the expansion of community health teams, comprising less-specialized health workers, increases preventive care and decreases curative care and preventable hospitalizations. We also estimate coverage improvements for previously unattended chronic conditions amenable to effective primary care. These results suggest that decentralization of tasks to less-specialized health workers improves efficiency, maintaining quality of care.
Keywords: I15; I18; H21; H51; 330; community-based healthcare; efficiency; coverage